Live birth rates are satisfactory following multiple IVF treatment cycles in poor prognosis patients - Mustafa, Kamarul Bahyah; Keane, Kevin Noel; Walz, Nikita L.; Mitrovic, Katarina I.; Hinchliffe, Peter M.; Yovich, John L. (Elsevier, 2017)
This seven-year retrospective study analysed the live birth rate (LBR) for women undergoing IVF treatment with various antral follicle counts (AFC). The LBR decreased with lower AFC ratings, and in 290 treatment cycles for women in the poorest AFC category, 4 follicles (group E), the LBR was the lowest at 10.7%. The pregnancy loss rate (PLR) significantly increased with poorer AFC categories, from 21.8% in AFC group A (20 follicles), to 54.4% in AFC group E (p < 0.0001). This trend was repeated with advancing age, from 21.6% for younger women ( < 35 years), to 32.9, 48.5 and 100% for ages 35–39, 40–44 and 45 years, respectively (p < 0.0001). However, LBR within the specific AFC group E cohort was also age-dependent and decreased significantly from 30.0% for <35 years old, to 13.3, 3.9 and 0% for patients aged 35–39, 40– 44 and 45 years, respectively. Most, importantly, LBR rates within these age groups were not dependent on the number of IVF attempts (1st, 2nd, 3rd or 4 cycles), which indicated that cycle number should not be the primary deciding factor for cessation of IVF treatment in responding women <45years old.